Psichologiceskie rezervy sportivnogo masterstva - Grigorjanc, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The author carried out questionnaire for the finding-out of the level of the psychological preparedness in the Russian sports gymnastics. The questionnaire has shown the lack of the knowledge of the psychology of gymnastics and the psychological training of athletes in many trainers. The same can be told about the efficiency of the education of students, specializing in sports gymnastics and in the educational course "psychology". It is necessary to analyze the education system of the future trainers-teachers and to determine, whether their volume of knowledge and skills is sufficient for the independent use of methods of the psychological training and to solve the elementary psychological problems in the practical work with athletes.